Homework : motivation and learning preference - Hong, Eunsook (Bergin & Garvey, 2000)
This work provides counsellors, classroom teachers and parents with an understanding of homework, as well as an introduction to homework methods and materials, in order to aid them in the challenge of helping children to do homework more effectively.